Conjunctive use of saline water for raising fennel (Foeniculum vulgare) and safflower (Carthamus tinctorius) on Vertic Ustochrept and Fluventic Eutrochrept soils of western India - Singh, Ravender; Bhargava, G P; Rao, G Gururaja (The Indian Journal of Agricultural Sciences, 2012)
A field experiment was conducted during the winter season (rabi) of 1992-93 and 1993-94 tostudy the effect of saline water on plant height and seed yield of 'Gujarat 1' fennel(Foeniculum vulgare Miller) and 'Bhima' safflower (Carthamus tinctorius L.). The electricalconductivity (EC) of saline water was 0.4 (pond water, considered best available water), 4,8, 12, 16 and 24 dS/m for Fluventic Eutrochrepl and 0.4, 4, 8, 12 and 16 dS/m for VerticUstochrept soils. Application of saline water of electrical conductivity 4, 8, 12, 16 and 24dS/m reduced the seed yield of fennel by 1.3, 2.4, 3.1, 4.1 and 13.7% respectively inFluventic Eutrochrept soil compared with pond water irrigation, and significant reduction infennel yield was observed with saline water of 16 dS/m. In Vertic Ustochrept soil the seedyield reduced by 8.7, 17.8, 26.9 and 36.8% with application of saline water of 4, 8, 12 and16 dS/m, and significant yield reduction was observed even at saline water of 4 dS/m. Insaline water the yield reduced by 9.0, 25.4, 34.6 and 45.0% in Vertic Ustochrept soil and by2.8, 6.2, 11.8, 23.7 and 37,8% in Fluventic Eutrochrept soil respectively with saline waterof 4, 8, 12 and 16 dS/m and significant yield reduction was observed with 8 dS/m.Application of saline water of increasing salinity and number of irrigations increased thesoil salinity up to a depth of 120 cm; however, the increase was more within the top 60 cmsoil.